Budgetary participation effect, budget emphasis, and information asymmetry on budgetary slack - Dinda Sheillaning Indira, Sri Ningsih, (Opción, 2020)
It is important for a management team to participate in the review and approval of a budget. Without their active participation in the approval process, there will be a substantial temptation for budgeters to “play around” with the budgetary system. To obtain empiric evidence for the assumption that budgetary participation, budget emphasis, and information asymmetry influenced the budgetary slack arising in the Organization of Gresik Local Government (OPD Gresik). The research results show that budgetary participation had a positive effect, budget emphasis had no effect, and information asymmetry had a negative effect on the budgetary slack arising within Gresik administration.